Tradisi Sodho Nderi pata Mata dalam Upacara Kematian Masyarakat Maunori Etnis Keo Kabupaten Nagekeo - Doi, Maksimilianus; Wanggai, Febe F. Irawati (LPPM STKIP PGRI Bandar Lampung, 2024)
This article discusses the tradition of death and its speech in conveying condolence messages to the family and social environment, and how condolence messages are conveyed by bereavement family messengers according to the status of kinship relations in the Maunori Ethnic Keo area, Nagekeo Regency. This research uses a qualitative descriptive method with an ethnographic approach. Data was collected through interviews and documentation. The results of the research show that in the death ritual tradition, the family whose condolences are conveyed are puu bheto (uncle of the dead's mother), embu mame/ine ame (uncle of the dead derived from the mother's lineage), tua eja wai daki (parents-in-laws, son-in-law, brother-in-law of the dead), and nua oda (local village residents). Speeches are interpreted in various ways depending on who the message of condolence is delivered to, and the impact of the message being conveyed is carried with it in accordance with the status of the kinship relationship.